1988
DOI: 10.1139/f88-085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Black Fly Ingestion and Assimilation on Seston Transport in a Quebec Lake Outlet

Abstract: Ingestion and assimilation rates of simullid (Diptera) larvae feeding on natural seston were estimated in an artificial stream and used to predict the impact of simuliids on seston transport in a 40-m section of the outlet stream of Petit Lac Fraser in southern Quebec. This prediction was then compared with changes in the seston flux above and below the population. Finally, we selectively killed simuliids with a larvicide (Bacillus thuringiensis serovar. israelensis) to observe changes in seston transport afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 8 publications
2
24
2
Order By: Relevance
“…Large standard error terms associated with the nonlinear regressions (as 95% CI in Table 1), lack replication in our field experiments, and small relative changes in k P all contributed to the low statistical power of our analysis. However, considering that POM capture rates (mg Ϫ1 filter-feeder dry mass) derived by back-calculating from the nonsignificant changes in k P were in close agreement with published values (e.g., Wotton 1978;McCullough et al 1979a,b;Morin et al 1988), we speculate that the observed changes in k P may have been real despite their lack of statistical significance.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Large standard error terms associated with the nonlinear regressions (as 95% CI in Table 1), lack replication in our field experiments, and small relative changes in k P all contributed to the low statistical power of our analysis. However, considering that POM capture rates (mg Ϫ1 filter-feeder dry mass) derived by back-calculating from the nonsignificant changes in k P were in close agreement with published values (e.g., Wotton 1978;McCullough et al 1979a,b;Morin et al 1988), we speculate that the observed changes in k P may have been real despite their lack of statistical significance.…”
Section: Discussionsupporting
confidence: 88%
“…These rates were higher than those observed by Morin et al (1988; particles Ͼ0.2 m; 1.13-1.53 g mg DM Ϫ1 min Ϫ1 ) and McCullough et al (1979a,b; diatoms and detritus of unreported size 0.2-1.33 g OM mg DM Ϫ1 min Ϫ1 ) but were similar to the range observed by Wotton (1978; powdered charcoal 10.1 m; 10.8-14 g OM mg DM Ϫ1 min Ϫ1 ).…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…Blackfly larvae are thus "allogenic ecosystem engineers" (Lawton and Jones 1995) and were probably responsible for the significant reduction in very small particles we recorded. Removal of particles < 11 pm in diameter was 0.06% m ' linear stream length, a much lower figure than the 0.8-1.4% m i of suspended matter recorded by Morin et al (1988) for a lake-outlet stream of similar depth (5-25 cm) in Canada.…”
Section: Notesmentioning
confidence: 60%
“…Shallow streams that support very high densities of suspension-feeders have a higher retention of suspended particles than do those without, and spiralling is a more important process as a result (Morin et al 1988;Wotton et al 1996). The highest population densities and production of suspension-feeders in fresh waters are found in shallow lake-outlet streams (Wotton 1994;Malmqvist and Eriksson 1995).…”
mentioning
confidence: 99%